Kevin Lynch and His Legacy on Teaching Professional Planners and Designers. Issue 3 (2nd October 2018) - Bosselmann, Peter
Abstract : Problem, research strategy, and findings: Here I highlight the continued relevance of Kevin Lynch's pedagogy through cultivating primary sources of information based on observation, field measurements, and interviews with users, especially at a time when information necessary for design decisions is available with increasing ease from secondary sources. Lynch's approach to teaching departed from solely studio-based pedagogies to include methods that drew from the city as a research laboratory. Lynch's tradition continued under Donald Appleyard at the University of California, Berkeley. Research required methodological foundations borrowed from the social sciences in the context of fieldwork and in the classroom. The environmental psychologist Kenneth H. Craik provided the necessary instruction. I summarize the research I have done over decades with urban design and planning students in the professional degree program at Berkeley.Takeaway for practice: Students following Kevin Lynch's research tradition are better prepared to articulate planning policy when instructed to combine subjective data gained through direct observation with objective data and with data collected onsite. Substantial professional attention was given to the results of multiple research methods seminars over the years; student research influenced official planning policy.